The role of tibolone in the treatment of ailments and diseases of the menopausal period - Stachowiak, Grzegorz; Pertyński, Tomasz (Menopause Review/Przegląd Menopauzalny, 2009)
Tibolone is a synthetic steroid having, apart from its estrogen activity, also affinity for progesterone and androgen receptors. Administered for climacteric syndrome and osteopenia/osteoporosis treatment of postmenopausal women, it is a good alternative for classic estrogen-progestagen hormone therapy, especially in older group of women after menopause, with increased breast cancer risk, low libido and vaginal spotting or bleedings during MHT.